The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/nhs.12549
|View full text |Cite
|
Sign up to set email alerts
|

Connection between organizational culture and climate and empowerment: The perspective of nurse managers

Abstract: Health-care organizations differ from other institutions due to their unique structure and management. Organizational culture and climate are the key constructs that compose the organizational social context, and might have an impact on employees, such as nurse managers, and the organization itself. The aim of this study was to analyze the connections between organizational culture and climate and work-related empowerment, and also to present culture and climate profiles at team and organization levels. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 30 publications
3
26
0
2
Order By: Relevance
“…Based on eta-squared values and ICC analysis, variations between organizations and groups seemed to be more within rather than between the groups. 30,40 The extent of negative ICC values both at the organizational and group level differed considerably. Only climate stress and cultural resistance differed significantly at group level.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Based on eta-squared values and ICC analysis, variations between organizations and groups seemed to be more within rather than between the groups. 30,40 The extent of negative ICC values both at the organizational and group level differed considerably. Only climate stress and cultural resistance differed significantly at group level.…”
Section: Discussionmentioning
confidence: 98%
“…29 As Trus et al. 30 mentioned, organizational culture and climate seemed to be connected with nurse manager work-related empowerment but at the same time Trus’s 31 research showed that nurse managers’ structural empowerment is only displayed on a moderate level.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with a previous study of Boyd (2017), which revealed that autonomy is an essential aspect of RNs' OC in the United States, involving self-determined controlled actions without any authorization by others. Nurse managers from Europe perceived that they were empowered both structurally and psychologically when the climate was engaged and functional (Trus et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…These are some of the strategies that may result in higher professional motivation and consequently, greater empowerment in the workplace. [22][23] One of this study's limitations refers to its cross-sectional design, which is related to confounding variables that may affect the relationships between the study variables. The study design is also sensitive to certain biases, such as desirability bias or a tendency in the responses of those people who voluntarily collaborated with the study.…”
Section: /14mentioning
confidence: 99%